Taboo lexical units in the online dictionaries Michaelis, Aulete, and Priberam - Orsi, Vivian [UNESP] (Assoc Nac Pos-graduacao Pesquisa Letras & Linguistica, 2021)
The lexicon of a language allows to see how the community perceives the world around it, in its different aspects. Within each lexical item, all information is posted and exposed. Thus, through its study, we can have an idea of preconceptions and taboos that are present in society. In this article, we try to understand the taboo units and their importance in the language, choosing to study the definition and the labels that come with to some lexical items that have one or more meanings considered offensive, and therefore taboos, within some entries, in the dictionaries available online Aulete, Michaelis and Priberam. Based on the theories of the two great sciences in which this research is included, Lexicology and Lexicography, we hope to bring some contribution to the discussion on the labels in dictionaries and the little attention they receive from lexicographers.
Keywords: Taboo Lexicon; Labels; Dictionaries